SARS-CoV-2 and Biosafety in Laboratory (Iraqi Journal of Medical Sciences, 2021)
The newly discovered coronavirus (Severe acute respiratory syndrome coronavirus-2, SARS-CoV-2) is the causative agent of the ongoing pandemic. Broad arrangement has been done to minimize virus spreading among population and to control the worldwide outbreak. Expanded biosafety measure specifically with respect to the work require using SARS-CoV-2 in laboratory (lab.) and a special consideration should be taken to protect researcher and lab. worker during handling of specimens. Therefore, the aim of this review is to help the scientists, researchers, lab. staff and biosafety specialists to respond to the current coronavirus disease (COVID-19) through discussion of effective biosafety practices that can prevent laboratory acquired infections and to lessen the spread of infection into community and environment.Keywords: Coronavirus, COVID-19, biosafety, research, laboratoriesCitation: Al-Shuwaikh AM, Al-Shwaikh RM, Hanna DB. SARS-CoV-2 and biosafety in laboratory. Iraqi JMS. 2021; 19(1): 1-9. doi: 10.22578/IJMS.19.1.1
Keywords: Coronavirus; COVID19; biosafety; research; laboratories